KEDUDUKAN ANAK TERHADAP HARTA WARISAN DALAM PERKAWINAN DI BAWAH TANGAN DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Safitri, Gusti Heliana; farizha, Nadia (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2019)
The problem in this study is the position of children born from marriageunder the hands and how the rights of children to inheritance frommarriage under the hands based on Law Number 1 of 1974 concerningMarriage. Underhand marriage is still happening in Indonesian society.Submarine marriage is a marriage that does not register the marriage tothe authorized institution, namely the Office of Religious Affairs forMuslims and the Civil Registry for non-Muslims. In Article 2 paragraph(2) of Law Num ber 1 of 1974 it is stated that a new marriage is valid if itis carried out according to the laws of each religion and its beliefs.However, the validity of marriage in the eyes of religion and public trustneeds to be ratified by the state in order to have legal force.The consequences of marriage under the hands are very bad forthe wife and for children born both legally, socially and psychologically.Other problems that can be caused from marriage under the hands are therights and obligations of husband and wife who are not guaranteed in fullfrom the State. The provisions in Article 42 paragraph (1) of Law Number1 Year 1974 concerning Marriage state that a legitimate child is a childborn from or as a result of a legal marriage. So it can be concluded thatchildren born from underage marriages are illegitimate children or out ofwedlock children. From the results of the research discussion it is knownthat Based on the Decision of the Constitutional Court Number 46 / PUUVIII/ 2010 Testing of Law Number 1 of 1974 concerning Marriage to theState Constitution of the Republic of Indonesia Year 194. It is said thatchildren born outside marriage have a civil relationship with his motherand his mother's family and with his man as his father that can be provenbased on science and technology and / or other evidence so according tothe law he has a blood relationship, including a civil relationship with hisfather's family